ASPECTS OF BEEF CONSUMPTION IN BRAZIL FROM THE PANDEMIC TO THE PRESENT DAY AND THE IMPACTS OF THIS FACTOR ON THE BRAZILIAN AGRIBUSINESS MARKET - passique, barbara; Bertaci, Moacir José (Revista Interface Tecnológica, 2024)
It is well known that the COVID-19 pandemic had significant impacts on the economy in a global context. However, for Brazilian agribusiness with regard to exports, there were no negative impacts. Very different from what one imagines, the agribusiness export market saw an increase in exports compared to the year 2019, which preceded the emergence of the Coronavirus pandemic. However, it is important to highlight that although exports were not impacted, in the domestic market some economic factors, such as unemployment, closing of bars and restaurants, high costs and others contributed to the drop in demand for beef. The objective of this study is to highlight the main impacts that the pandemic brought to the domestic beef market in Brazil. The methodology used was Literature Review with consultations in articles displayed on Google Scholar and SciELO, as well as on websites that deal with the subject specifically. The results indicate that agribusiness did not suffer negative impacts from the atypical phase experienced, since exports remained stable or even grew. The main impacts were related to the domestic market.